Secure Communications Over Wireless Broadcast Networks - Singh, Vikram; Ramola, Jaspal (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2014)
Wireless telecommunications is the transfer of information between two or more points that are not physically connected. Distances can be short, such as a few meters for television remote control, or as far as thousands or even millions of kilometers for deep-space radio communications. In this paper wireless broadcast network model(WBN) with secrecy constraints is investigated, in which a source node broadcasts confidential message flows to user nodes, with each message intended to be decoded accurately by one user and to be kept secret from all other users. In the existing system we developed, and implemented a compromised router detection protocol (DP) that dynamically infers, based on measured traffic rates and buffer sizes, the number of congestive packet losses (CPL) that will occur. Each and every packet is encrypted so that to prevent the data from eavesdropping. So the data is much secured.